Herpes genitalis and circumcision. Issue 4 (August 1975) - Taylor, P K; Rodin, P
Abstract : 214 patients with genital herpes infection proven by culture and a control group of 410 other patients were included in a retrospective study devised to investigate the relationship of circumcision to genital HSV infection in the male. The percentage of patients circumicised in the control group was significantly larger than in the herpes group (P less than 0-01). The was not found to be the case for other sexually-transmitted diseases apart from monilial balanitis. There was also a significant difference in contraceptive methods in the two groups, barrier methods being used less ofter than other methods in the herpes group and the reverse in the control group. It is concluded that there is a positive relationship between absence of circumicision and genital HSV infection, but that a prospective study should be undertaken to confirm these results.